Synthesis of frequency diverse array with large null depths via a hybrid optimisation approach of mayfly algorithm and convex programing - Xiaolang Shao; Taiyang Hu; Jinyu Zhang; Zelong Xiao (IET Signal Processing, 2022)
Abstract By controlling the null distribution in the range‐angle dimension, the frequency diverse array (FDA) can handle range‐dependent interference, which is usually difficult to solve for the traditional phased array. However, the current investigations focus more on the design of weights for null control, ignoring the unique design dimension of FDA, that is, the frequency offsets. Therefore, the array potential cannot be fully exploited to maximise the range‐dependent interference suppression capability. In this paper, a novel FDA synthesis method with large null depth is proposed. By incorporating the mayfly algorithm and convex programing, frequency offsets and transmit weights are jointly optimised to generate maximum null depths in a given region while maintaining the specified array response of the desired target. Other null control methods for FDA are listed as comparison, including weights‐only optimisation method, frequency offsets‐only optimisation and frequency offsets and weights sequentially optimisation method. Numerical examples demonstrate the superiority of the proposed algorithm.